“Smile and please hide your sickness”: The role of emotions and sickness surface acting in a presenteeism climate context. - Correia Leal, C.; Ferreira, A.I.; Carvalho, H. (80th Annual Meeting of the Academy of Management, 2020)
The study of emotional labor and presenteeism climates in the hotel business is critical due to nowadays context of economic insecurity, that obliges people to continue to show up for work even when they feel sick. Our study findings underline the value of policies creation to reduce and manage the negative effects of negative emotions and presenteeism climates, as well enlighten managers of the negative impacts of “service with a smile” and sickness presenteeism for the hotel businesses.